Trichoderma harzianum as a growth enhancer of oil palm and factors affecting its mass production - Rusli, Mohd Hefni (2008)
The oil palm industry is one of the highest users of chemical-based fertilizers and pesticides in Malaysia. This study was conducted to investigate the effect of formulated Trichoderma (FA 1132) as an alternative biofertilizer for use in the industry. A nursery trial was conducted at the glasshouse in Universiti Putra Malaysia (UPM), using a total of 45 seedlings. Six treatments were carried out to determine the effect of the formulated Trichoderma as a growth enhancer; the first 3 were single applications each of the formulated Trichoderma (strain FA 1132), commercial compost and chemical fertilizers respectively. The second consisted of mixed treatments of 1:1 Trichoderma formulation with fertilizers and 1:1 of the formulation with commercial compost. Five growth parameters assessed were increased stem girth, frond number, frond length, number of pinnae/longest frond and leaf chlorophyll content. The experiment was arranged in a Randomized Complete Block Design (RCBD) at 3 replicates of 15 seedlings per treatment. Results showed that the best growth enhancer of oil palm seedlings was the treatment with the formulated Trichoderma. The same treatments and parameters were used for field trial I at Taman Pertanian Pertanian Universiti (TPU), UPM; a forest clearing area and has never been planted with any crops before. The experiment was conducted in a RCBD at 3 replicates with 9 palms per subplot. Results showed that the application of the Trichoderma formulation again was the best growth enhancer of the oil palms compared to other treatments. In Mungka Estate, Segamat, Johor by using the same treatments as Field Trial I, experimental design set up in RCBD at 4 replicate plots of 20 palms per subplot, results showed that the mixed formulation, 1:1 Trichoderma formulation with fertilizers ranked the highest in terms of efficacy as the growth enhancer of oil palms. Field Trial II was actually an ex-oil palm field for second generation planting and may therefore have nutrient deficiency soils. In order to mass produced conidia of FA 1132, a submerged fermentation using potato sucrose broth as a media with 9% of molasses as nutrient supplement was conducted. It was stirred at an impeller speed of 750rpm and a dissolved oxygen tension rate of 75%. The results showed an increment to 4.6 x 109 conidia/ml per hour after 84 hours from 3.2 x 107 conidia/ml. Laboratory studies also conducted to optimize the production of FA 1132 conidia in solid state fermentation with an intention towards the development a suitable medium to replace palm fibers as the solid substrate medium for the production of FA 1132 and better suit for liquid formulation. Results found 500g milled rice at 100% moisture content with 9% molasses as a nutrient supplement and stirred homogenously at day six gave the best conidia counts at 107 conidia/ml stock in 14 days.